Magnetic resonance imaging diagnosis and parasitological verification of human suborbital dirofilariasis - Mitko A. MITEV (Archives of the Balkan Medical Union, 2020)
Introduction. The presence of mosquitoes and the abundance of microfilariae in dogs are considered of great risk for invading humans with dirofilariasis. We present an extremely rare case of Dirofilaria repens in the periorbital subcutaneous area, diagnosed for the first time in Bulgaria by magnetic resonance imaging (MRI).